Implementasi Pembelajaran Kurikulum Merdeka Penguatan Karakter Sebagai Identitas Budaya Bangsa - Hayatuddin, Hayatuddin; Hamid, Abdul; Saputra, Eddy; Ali, Nur (SAP (Susunan Artikel Pendidikan), 2025)
The Merdeka Curriculum is an educational approach that aims to develop students' potential holistically by paying attention to local wisdom and national character. Merdeka curriculum learning also emphasizes national identity and culture as an important part of education. Through learning about history, culture, and traditional values, students are given a deeper understanding of the identity and cultural richness of their nation. This aims to strengthen the feeling of love for the country, foster a sense of unity, and maintain cultural diversity in Indonesia. Independent Curriculum Learning is an approach promoted in an effort to strengthen the essence of education, which includes character development and strengthening national identity and culture. This research uses descriptive analytical methods with a qualitative approach to explore various literature and policies related to independent curriculum learning. The aim of this research is to show the need for curriculum development that is responsive to the contextual needs of society as well as strengthen the role of teachers in implementing independent curriculum learning effectively at the formal education level.